2012
DOI: 10.2174/1876400201205010019
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Temperature on the Long-Term Behaviour of Waste Degradation, Emissions and Post-Closure Management Based on Landfill Simulators

Abstract: A demonstration pilot with seven anaerobic landfill simulators (LSRs) was used to study the impact of temperature in the range of 20 -46 °C on long-term landfill emissions, characteristics and tendencies, because of an evident lack of knowledge in this area. The pilot ran more than 1400 days. Higher temperatures accelerated the waste degradation and gas generation, but also resulted in higher leachate COD and NH 4 -N concentrations, which will prolong the aftercare period in order to meet the effluent discharg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 23 publications
(32 reference statements)
1
10
0
Order By: Relevance
“…In general, waste temperatures were cooler toward the ground surface, increased to a maximum temperature at the middle depths of the waste mass, and then decreased as depth approached the bottom liner. Overall, measured waste temperatures were similar to those reported in the literature (Yesiller et al 2005;Hanson et al 2010a;Yesiller et al 2011;Wang et al 2012). …”
Section: Temperaturesupporting
confidence: 85%
See 3 more Smart Citations
“…In general, waste temperatures were cooler toward the ground surface, increased to a maximum temperature at the middle depths of the waste mass, and then decreased as depth approached the bottom liner. Overall, measured waste temperatures were similar to those reported in the literature (Yesiller et al 2005;Hanson et al 2010a;Yesiller et al 2011;Wang et al 2012). …”
Section: Temperaturesupporting
confidence: 85%
“…The distribution and range of waste temperatures with depth is illustrated by the curvilinear relationship presented in Figure 2.12. Several studies presented in the literature suggested a correlation exists between optimal temperature and elevated waste degradation and gas production to an extent (Rees 1980;Hartz et al 1982;Mata-Alvarez and Martinez-Viturtia 1986;Blakey et al 1997;Yesiller et al 2011;Wang et al 2012). …”
Section: Temperaturementioning
confidence: 99%
See 2 more Smart Citations
“…The decomposition of waste material depends upon biochemical processes and other parameters such as time, temperature, and moisture content (Fatta et al, 1999;Karthikeyan et al, 2008;Wang et al, 2012a). Pollution from landfills is associated with waste composition, and in India, organic waste (wet waste) has a greater share (>50%) of the total composition (Joshi and Ahmed, 2016).…”
Section: Introductionmentioning
confidence: 99%